A companion to sport and spectacle in Greek and Roman antiquity - Christesen, Paul, 1966-; Kyle, Donald G. (Chichester, West Sussex, UK : Wiley Blackwell, 2014)
"A Companion to Sport and Spectacle in Greek and Roman Antiquity presents a series of essays that apply a socio-historical perspective to myriad aspects of ancient sport and spectacle. Covers the Bronze Age to the Byzantine Empire. Includes contributions from a range of international scholars with various Classical antiquity specialties. Goes beyond the usual concentrations on Olympia and Rome to examine sport in cities and territories throughout the Mediterranean basin. Features a variety of illustrations, maps, end-of-chapter references, internal cross-referencing, and a detailed index to increase accessibility and assist researchers"--
General Introduction / Paul Christesen and Donald G. Kyle -- Section One. Greece -- Part One. The Background -- Greek Athletic Competitions : The Ancient Olympics and More / Donald G. Kyle -- Sport in the Aegean Bronze Age / Jeremy B. Rutter -- Sport in the Early Iron Age and Homeric Epic / Timothy P.J. Perry -- Representations of Sport in Greek Literature / Nigel Nicholson -- Picturing Victory : Representations of Sport in Greek Art / Jenifer Neils -- Inscriptions as Evidence for Greek Sport / H.W. Pleket -- Recent Trends in the Study of Greek Sport / Ingomar Weiler -- Part Two. Places -- Panhellenic Athletics at Olympia / Thomas Heine Nielsen -- Sport and Society in Sparta / Paul Christesen -- Sport, Society, and Politics in Athens / Donald G. Kyle -- Athletic Festivals in the Northern Peloponnese and Central Greece / David Gilman Romano -- Sport and Society in the Greek West / Carla M. Antonaccio -- Part Three. People, Settings, Ideas -- Sport and Democratization in Ancient Greece (with an Excursus on Athletic Nudity) / Paul Christesen -- Growing Up with Greek Sport : Education and Athletics / Werner Petermandl -- Eros and Greek Sport / Andrew Lear -- Greek Female Sport : Rites, Running, and Racing / Donald G. Kyle -- People on the Fringes of Greek Sport / Christian Mann -- The Greek Stadium as a Reflection of a Changing Society / Stephen G. Miller -- The Social Life of Greek Athletic Facilities (other than Stadia) / Michael Scott -- The Role of Religion in Greek Sport / Sarah C. Murray -- Ancient Critics of Greek Sport / Zinon Papakonstantinou -- Sport, Spectacle, and Society in Ancient Macedonia / Winthrop Lindsay Adams -- Part Four. Later Greek Sport and Spectacle -- Greek Sport in Egypt : Status Symbol and Lifestyle / Sofie Remijsen -- Sport in Hellenistic and Roman Asia Minor / H.W. Pleket -- Section Two. Rome -- Part One. The Background -- Overview of Roman Spectacle / Roger Dunkle -- Etruscan Sport / Giampiero Bevagna -- Writing Arenas : Roman Authors and Their Games / Zara Martirosova Torlone -- Representations of Spectacle and Sport in Roman Art / Steven L. Tuck -- Material Evidence for Roman Spectacle and Sport / Gregory S. Aldrete -- Trends in the Study of Roman Spectacle and Sport / Jerry Toner -- Part Two. Spectacles and Sport in Rome -- Gladiatorial Combat as Alluring Spectacle / Garrett G. Fagan -- Women with Swords : Female Gladiators in the Roman World / Stephen Brunet -- Roman Chariot Racing : Charioteers, Factions, Spectators / Sinclair Bell -- Roman Beast-Hunts / Chris Epplett -- Spectacular Executions in the Roman World / Chris Epplett -- Greek Sports in Rome / Hugh M. Lee -- Part Three. People, Settings, Ideas -- Amphitheaters in the Roman World / Hazel Dodge -- Venues for Spectacle and Sport (other than Amphitheaters) in the Roman World / Hazel Dodge -- People on the Margins of Roman Spectacle / Rose MacLean -- Religion and Roman Spectacle / John Zaleski -- Ancient Critics of Roman Spectacle and Sport / Kathryn Mammel -- Part Four. Later Roman Spectacle and Sport -- Romanization through Spectacle in the Greek East / Michael Carter -- Spectacle and Sport in Constantinople in the Sixth Century CE / David Alan Parnell.
Includes bibliographical references and index.
Print version record.
Keywords: To 146 B.C.; Antiken; Sports -- Greece -- History; Sports -- Rome -- History; Sports -- Social aspects -- Greece -- History; Sports -- Social aspects -- Rome -- History; Sports -- Greece -- History; Sports -- Rome -- History; Sports -- Social aspects -- Greece -- History; Sports -- Social aspects -- Rome -- History; GAMES -- Gambling -- Sports; SPORTS & RECREATION -- Business Aspects; SPORTS & RECREATION -- Essays; SPORTS & RECREATION -- History; SPORTS & RECREATION -- Reference; TRAVEL -- Special Interest -- Sports; Manners and customs; Social conditions; Sports; Sports -- Social aspects; Idrott -- historia; Greece -- Social life and customs; Rome -- Social life and customs; Greece -- Social conditions -- To 146 B.C.; Rome -- Social conditions; Greece; Rome (Empire); Multi-User.; Electronic books; History